1993
DOI: 10.1002/aoc.590070203
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of binuclear ferrocene derivatives

Abstract: On the basis of an earlier model of chemical carcinogenesis, the antitumor activity of the mono-, bi-and poly-nuclear ferrocene derivatives ferricenium tri-iodide (l), ferricenium tetrachloroferrate (2), 1,l'-diethylferricenium triiodide (3), N-(ferrocenylmethy1)hexamethylenetetramine tetrafluoroborate (4), bis(ferrocenylmethy1)benzotriazolium tetrafluoroborate (3, bis(ferroceny1-a-ethy1)benzotriazolium tetrafluoroborate (6) and bis(ferrocenylmethyl)-2-methylbenzimidazolium tetrafluoroborate (7), and the oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 10 publications
0
52
1
Order By: Relevance
“…All the compounds (1-12) showed low toxicity because %cell viability was above 50%. This is not surprising because it had earlier been reported that ferrocenyl derived compounds do possess low toxicity [46]- [48]. …”
Section: Resultsmentioning
confidence: 69%
“…All the compounds (1-12) showed low toxicity because %cell viability was above 50%. This is not surprising because it had earlier been reported that ferrocenyl derived compounds do possess low toxicity [46]- [48]. …”
Section: Resultsmentioning
confidence: 69%
“…22 Promising activity behavior was reported independently for the tetrachloroferrate 23 and for the triiodide, 24 with therapeutic indices appreciably larger than determined for cisplatin. Lastly, activity was shown by certain azole derivaties of ferrocene which could potentially exist in a form featuring a cationic site.…”
mentioning
confidence: 92%
“…The incorporation of (methylamino)benzonitrile and N-methylnitroaniline in a ferrocene moiety could provide new derivatives with important biological activities since several ferrocene derivatives have already been shown to be active against a number of tumors [17][18][19]. Herein we report the synthesis, characterization and electrochemical behavior of a series of N-(ferrocenylmethyl)aminobenzonitrile and N-(ferrocenylmethyl)nitroaniline derivatives which combiFne the ferrocene moiety with (methylamino)benzonitrile and N-methylnitroaniline groups.…”
Section: Introductionmentioning
confidence: 99%